2012
DOI: 10.1088/0004-637x/750/1/2
|View full text |Cite
|
Sign up to set email alerts
|

CRITICAL EVALUATION OF MAGNETIC FIELD DETECTIONS REPORTED FOR PULSATING B-TYPE STARS IN LIGHT OF ESPaDOnS, NARVAL, AND REANALYZED FORS1/2 OBSERVATIONS

Abstract: Recent spectropolarimetric studies of seven slowly pulsating B (SPB) and β Cep stars have suggested that photospheric magnetic fields are more common in B-type pulsators than in the general population of B stars, suggesting a significant connection between magnetic and pulsational phenomena. We present an analysis of new and previously published spectropolarimetric observations of these stars. New Stokes V observations obtained with the high-resolution ESPaDOnS and Narval instruments confirm the presence of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…The first reliable detection was confirmed with ESPaDOnS data by Shultz et al (2012). Here we report for the first time the detection of a magnetic field in both components of ǫ Lupi, making it the first known close binary with two magnetic, massive stars.…”
Section: Introductionsupporting
confidence: 57%
“…The first reliable detection was confirmed with ESPaDOnS data by Shultz et al (2012). Here we report for the first time the detection of a magnetic field in both components of ǫ Lupi, making it the first known close binary with two magnetic, massive stars.…”
Section: Introductionsupporting
confidence: 57%
“…The star HD 46328 (ξ 1 CMa) is a β Cep star (Saesen et al 2006) for which the presence of a magnetic field has first been reported by Hubrig et al (2006Hubrig et al ( , 2009. This was further confirmed by high-resolution spectropolarimetry (Silvester et al 2009;Fourtune-Ravard et al 2011;Shultz et al 2012). Hubrig et al (2011) used the FORS1 measurements to model the magnetic field of HD 46328, assuming a dipolar configuration of the magnetic field.…”
Section: Magnetic Field Detection Ratementioning
confidence: 83%
“…The LSD profiles are therefore sensitive even to the field topologies that yield very low or null mean longitudinal fields (e.g. Shultz et al 2012). The LSD method has been successfully used to detect and map complex dynamo-generated magnetic fields of cool active stars (Donati et al 2003;Kochukhov et al 2013).…”
Section: Methodsmentioning
confidence: 99%